Maternal personal hygiene as a dominant risk factor for diarrhea among toddler in Medan City: a logistic regression analysis - Sufia Idya; Jayanti Rida Lestari; Rahmi Wardani (Talenta Publisher, 2026)
In Indonesia, toddler diarrhea is still a major public health concern, especially in crowded cities like Medan City. The prevalence of diarrhea in toddlers remains high despite advancements in environmental sanitation, suggesting the impact of additional contributing factors, particularly caregiver behavior. The purpose of this study was to examine the main variables linked to toddler diarrhea incidence, with an emphasis on maternal personal hygiene habits. In this quantitative study, 120 mothers with toddlers ages 24 to 59 months selected through purposive sampling participated in a cross-sectional design. Participants were chosen from Medan City's seven subdistricts with the highest number of toddler diarrhea cases reported. Maternal personal hygiene behavior—which includes knowledge, attitudes, and practices—were the independent variables. Multiple logistic regression analysis was used to determine the most significant factor influencing the incidence of diarrhea in toddlers. The findings indicated that maternal personal hygiene practices were the most significant factor linked to toddler diarrhea incidence among all variables analyzed (p = 0.013; Exp.B = 3.387). Diarrhea was 56% more likely to occur in toddlers whose mothers practiced poor personal hygiene. The incidence of diarrhea was not substantially correlated with maternal attitudes or environmental sanitation factors. In conclusion, preventing diarrhea in toddlers in urban environments requires improving maternal hygiene practices, especially handwashing with soap, sterilizing baby bottles and feeding utensils, and preparing safe food and drinking water.